Temperatura base, crescimento, desenvolvimento de crambe (Crambe abyssinica Hochst ex R.E. Fries) - Silveira, Tatiani Reis da (2012)
The crambe is an oilseed that belongs to the Brassicaceae family, is considered a winter crop, with good tolerance to frost. In the state of Rio Grande do Sul, missing information on the growth, development and adaptation of crambe, which limits the adoption by producers of culture. The knowledge of thermal and base temperature scale allows the crop cycle, helping to define the sowing date and correct timing of the implementation of management practices. Thus, this study aims to evaluate and characterize the growth and development of crambe, to determine the thermal over the cycle and by different methods to estimate the base temperature for the cultivar Brilliant FMS. An experiment was conducted at the Federal University of Santa Maria, in the years 2010 and 2011, the following sowing dates: 06/10/2010, 07/05/2010, 08/03/2010, 08/19/2010, 09/09/2010, 09/17/2010, 02/18/2011, 04/06/2011, 04/28/2011, which was evaluated twice a week the phenological stage of the height and number of leaves of 20 plants each time. Using daily temperature data, we calculated the basis for the subperiods temperature sowing-emergence, emergence, flowering, fruiting, flowering, fruit-maturation and maturation-emergency, by traditional methods: a smaller deviation in degree-days, the lower standard deviation days, X-intercept, coefficient of variation in degree-day coefficient of variation in days and the regression coefficient; by methods modified by Yang et al. (1995), which are offset in degree-days, lower standard deviation in days , coefficient of variation in degree-days and the regression coefficient, and proposed new methods: pseudopseudo- sigma and sigma in days. The method estimated more accurately subperiods higher, with the temperature average basis for emergency subperiod maturation of 4.5 ° C. The increase both in height and in the number of sheets is down to 300 ° days, thereafter the plants grew faster variable up to about 900 ° days, when the stabilizing time and the number of sheets decreases because of senescence.